Genre Knowledge and Writing Development: Results From the Writing Transfer Project. (January 2020) - Driscoll, Dana Lynn; Paszek, Joseph; Gorzelsky, Gwen; Hayes, Carol L.; Jones, Edmund
Using a mixed-methods, multi-institutional design of general education writing courses at four institutions, this study examined genre as a key factor for understanding and promoting writing development. It thus aims to provide empirical validation of decades of theoretical work on and qualitative studies of genre and the nature of genre knowledge. While showing that both simplistic and nuanced genre knowledge promote writing development, our findings suggest that nuanced genre knowledge correlates with writing development over the course of a semester. Based on these findings, we propose an expanded view of Tardy's four genre knowledge components and argue for their explanatory power. We recognize these genre components can be cultivated by using three particular strategies: writing for nonclassroom audiences, using source texts explicitly to join existing disciplinary conversations, and cultivating two types of metacognitive awareness (awareness of the writing strategies used to complete specific tasks and awareness of one's levels of proficiency in particular types of writing knowledge). Findings can be used to enrich first-year or upper-division writing curricula in the areas of genre knowledge, audience awareness, and source use.